Handbook of Smart Materials, Technologies, and Devices Applications of Industry 4.0 - Hussain, Chaudhery Mustansar; Di Sia, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This handbook brings together technical expertise, conceptual background, applications, and societal aspects of Industry 4.0: the evolution of automation and data exchange in fabrication technologies, materials processing, and device manufacturing at both experimental and theoretical model scales. The book assembles all the aspects of Industry 4.0, starting from the emergence of the concept to the consequences of its progression. Drawing on expert contributors from around the world, the volume details the technologies that sparked the fourth revolution and illustrates their characteristics, potential, and methods of use in the industrial and societal domains. In addition, important topics such as ethics, privacy and security are considered in a reality where all data is shared and saved remotely. The collection of contribution serve a very broad audience working in the fields of science and engineering, chemical engineering, materials science, nanotechnology, energy, environment, green chemistry, sustainability, electrical and electronic engineering, solid-state physics, surface science, aerosol technology, chemistry, colloid science, device engineering, and computer technology. This handbook ideal reference libraries in universities and industrial institutions, government and independent institutes, individual research groups and scientists.
Industry 4.0: Concepts, Themes and Perspectives -- Industry 4.0: Mode of Materials, Technology & Devices -- Industry 4.0: Applications -- Industry 4.0: Concept of Smart, Intelligent & Sustainable Society -- Industry 4.0: Dangers/warning points.
Keywords: Industrial engineering; Production engineering; Nanoscience; Materials; Automation; Industrial and Production Engineering; Nanophysics; Materials for Devices; Industrial Automation; Industry 4.0.; Technological innovations -- Social aspects